Optimización de los procesos para la reducción de costos en la empresa de servicios G & S INGENIEROS CÍA. LTDA. - Herrera Unaucho, Cristian Joel (2018)
The present research has as aim the optimization of the processes which contribute with the reduction of costs through the decrease in times of each one of the activities that interfere in the construction of electrical projects in the company G&S INGENIEROS CIA LTDA. It was analyzed how to optimize the electrical projects construction processes through a times study which allowed the reduction of investment costs, and then plant an improvement proposal in the times of work length in every process through the development of times standardization, achieving a considerable increase in its profits. The study proposed was planted as a nonexperimental inquiry, an analytic and inductive methodology were adopted where a thorough analysis of documents was made and contributed with the identification of the current state of the company. The outcomes allowed to identify the high times that the development of each activity takes proposing a standardization of times in the fulfillment of activities in order to achieve a decrease in the workforce costs of about 4921, 40 dollar nowadays to 4784, 50 dollar, with the proposal planted there will be a saving of 136, 70 dollar per project. Through the development of this research project, it can be concluded that when a standardization of times is implemented in the processes of electrical projects construction the investment costs reduce permitting so that the company increase its profit per project through a better efficiency in its staff and the development of the activities in a lower time